INFLUENCE OF LEARNING MODEL DISCOVERY LEARNING AGAINST STUDENT RESULTS IN CONTENT TYPE AND CLASSIFICATION OF STEEL IN ARCHITECTURE ENGINEERING CLASS X SMKN 1 PALANGKA RAYA 2014/2015 - Yulianty; Lola Cassiophea (Jurusan Pendidikan Teknologi Dan Kejuruan, 2015)
Learning outcomes Based on the observations of the current researchers Practice Experience (PPL) and interviews with subject teachers Building Construction SMK 1 Palangkaraya, obtained information that the majority of students are less eager to absorb the lessons Building on the material type and classification steel. This is due to the tendency of teachers presenting the material directly, so that learners are not actively involved in learning. This can be seen from the value of student learning outcomes in subjects Building Materials class X Architecture Engineering SMK 1 Palangkaraya Academic Year 2014/2015 on the material type and classification of steel which is still relatively low. From some of these problems, so in this study used a model of learning discovery learning in hopes of making learning material types and classification of steel more meaningful and fun. So as to make students actively involved during the learning process and the classification of the type of steel in the classroom so that student learning outcomes increases. This study used a quasi-experimental research designs Nonequivalent type Control Group Design. The population in this study were all students of class X engineering drawings SMK- 1 Palangkaraya totaling 28 students. Sampling was carried out using saturated sampling technique in which all members of the population being sampled. Design approach used is a quantitative approach. This study was conducted in December to February 2015. The data is taken from the data of student learning outcomes obtained through the covers pretest and posttest. Based on the results of research conducted in class X drawing technique building with 28 students, there is a difference between the experimental class and the control class. It can be seen from the average value of students being taught by learning discovery learning model is better than being taught by conventional learning, where the average value of the experimental class at 90.19, while the average value of 74 control class.